Deriving protein binding‐corrected chemical concentrations for in vitro testing - Aditya R. Kolli (Wiley, 2023)
Abstract Extracellular chemical concentrations are considered physiologically relevant for in vitro testing and are evaluated in traditional in vitro systems using cell culture media containing 5%-10% fetal bovine serum (FBS). However, depending on the physicochemical properties, and in vitro testing conditions, cells could be exposed to variable unbound extracellular concentrations. If in vitro unbound concentrations are not calculated, it is challenging to distinguish the chemical potency and concentration‐driven responses. In this study, one‐ and two‐protein binding models were used to estimate protein binding corrected chemical concentrations of various chemicals for in vitro testing. As ceftizoxime, moxifloxacin, and nicotine have low protein binding affinity, the in vitro protein binding in 5%-10% FBS is less than 5% and can be considered negligible. However, protein binding of moderate and highly protein‐bound chemicals must be corrected for as the in vitro unbound concentrations in 5%-10% FBS containing cell culture media will vary over a range of chemical concentrations. In vitro pharmacological and toxicological assessments must incorporate protein binding‐adjusted in vitro concentrations to ensure physiologically relevant exposures. A user‐friendly Excel spreadsheet is provided to help bench scientists calculate protein binding‐corrected chemical concentrations for in vitro testing.